Implementasi Pembelajaran Daring di Sekolah Dasar Negeri 1 Lurah Kecamatan Plumbon Kabupaten Cirebon - Ani Ardiani; Iffan Ahmad Gufron (EduBase : Journal of Basic Education, 2021)
In March there was a disaster that befell Indonesia and even the world due to a disease outbreak in the form of the corona virus (COVID19). Some of the things affected by the virus, one of which is education, in March the government imposed learning at home. This study aims to determine the driving and inhibiting factors of the use of information and communication technology as a medium in online learning at schools. The method used is descriptive qualitative research and the design used in this research is phenomenology. The research was conducted at the State Elementary School 1 Lurah, Plumbon District, Cirebon Regency, with several students as research subjects. Based on the results of the analysis concluded First, the use of information and communication technology as a medium in online learning which is implemented in the Elementary School 1 Lurah Plumbon District, Cirebon Regency has been established since the beginning of March 2020. Second, regarding the driving and inhibiting factors that will make the process of implementing information and communication technology necessary the process of time is not small, besides it requires collaboration between the principal, teachers, students as well as parents of students. Abstrak Pada bulan maret terjadi sebuah musibah yang menimpa indonesia bahkan dunia akibat wabah penyakit berupa virus corona (COVID19). Beberapa hal terdampak karena virus tersebut salah satunya adalah pendidikan, pada bulan maret pemerintah memberlakukan belajar dirumah dengan cara online. Penelitian ini bertujuan untuk mengetahui faktor yang menjadi pendorong dan penghambat dari pemanfaatan teknologi informasi dan komunikasi sebagai media dalam pembelajaran daring di Sekolah. Metode yang digunakan adalah penelitian kualitatif yang bersifat deskriptif dan desain yang digunakan dalam penelitian ini adalah fenomenologi. Penelitian dilakukan di Sekolah Dasar Negeri 1 Lurah Kecamatan Plumbon Kabupaten Cirebon, dengan subyek penelitian beberapa siswa. Berdasarkan hasil analisis diperoleh kesimpulan. Pertama pemanfaatan teknologi informasi dan komunikasi sebagai media dalam pembelajaran daring yang di terapkan di Sekolah Dasar Negeri 1 Lurah Kecamatan Plumbon Kabupaten Cirebon telah ditetapkan sejak awal bulan maret 2020. Kedua, mengenai faktor pendorong dan penghambat yang akan menjadikan proses dalam menerapkan teknologi informasi dan komunikasi butuh proses waktu yang tidak sedikit, selain itu membutuhkan kerjasama antara kepala sekolah, guru-guru, peserta didik juga orang tua peserta didik